First true brackish-water nudibranch mollusc provides new insights for phylogeny and biogeography and reveals paedomorphosis-driven evolution - Korshunova, Tatiana; Lundin, Kennet; Malmberg, Klas; Picton, Bernard; Martynov, Alexander (PLOS ONE, 2018)
A unique example of brackish water fjord-related diversification of a new nudibranch genus and species Bohuslania matsmichaeli gen. n., sp. n. is presented. There are only few previously known brackish-water opisthobranchs and B. matsmichaeli gen. n., sp. n. is the first ever described brackish-water nudibranch with such an extremely limited known geographical range and apparently strict adherence to salinity levels lower than 20 per mille. Up to date the new taxon has been found only in a very restricted area in the Idefjord, bordering Sweden and Norway, but not in any other apparently suitable localities along the Swedish and Norwegian coasts. We also show in this study for the first time the molecular phylogenetic sister relationship between the newly discovered genus Bohuslania and the genus Cuthona. This supports the validity of the family Cuthonidae, which was re-established recently. Furthermore, it contributes to the understanding of the evolutionary patterns and classification of the whole group Nudibranchia. Molecular and morphological data indicate that brackish water speciation was triggered by paedomorphic evolution among aeolidacean nudibranchs at least two times independently. Thus, the present discovery of this new nudibranch genus contributes to several biological fields, including integration of molecular and morphological data as well as phylogenetic and biogeographical patterns.